2006
DOI: 10.1080/01926230600611794
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Irradiation-Induced Tumor Susceptibility in Brca2 Germline Mutant Mice and Cooperative Effects with a p53 Germline Mutation

Abstract: Mutations in both p53 and BRCA2 are commonly seen together in human tumors suggesting that the loss of both genes enhances tumor development. To elucidate this interaction in an animal model, mice lacking the carboxy terminal domain of Brca2 were crossed with p53 heterozygous mice. Females from this intercross were then irradiated with an acute dose of 5 Gy ionizing radiation at 5 weeks of age and compared to nonirradiated controls. We found decreased survival and timing of tumor onsets, and significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Homozygous deletion of exon 27 in mice resulted in the development of various epithelial carcinomas, lymphomas and sarcomas however, no osteosarcomas and only one ovarian tumor were reported (McAllister et al, 2002). In contrast, further studies showed significantly more osteosarcomas in homozygous mice lacking exon 27 than in their heterozygous or wild-type counterparts, an effect that was greatly enhanced when the mice were also heterozygous for mutant p53 (McAllister et al, 2006). These authors point out that tumor spectrum in these models may be affected by the background strain genetics.…”
Section: Discussionmentioning
confidence: 97%
“…Homozygous deletion of exon 27 in mice resulted in the development of various epithelial carcinomas, lymphomas and sarcomas however, no osteosarcomas and only one ovarian tumor were reported (McAllister et al, 2002). In contrast, further studies showed significantly more osteosarcomas in homozygous mice lacking exon 27 than in their heterozygous or wild-type counterparts, an effect that was greatly enhanced when the mice were also heterozygous for mutant p53 (McAllister et al, 2006). These authors point out that tumor spectrum in these models may be affected by the background strain genetics.…”
Section: Discussionmentioning
confidence: 97%
“…Inactivation of p53 acts cooperatively with genetic alterations in other tumor suppressor or oncogenes to increase cancer risk (43). In this study, we showed that RAP80 −/− p53 −/− double knockout mice exhibited a greater decrease in tumor-free survival compared to p53 −/− single knockout mice indicating that the loss of RAP80 acts synergistically with the loss of p53 in promoting spontaneous lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
“…The strength and nature of each driver is distinct. For example, p53 and Notch can drive OS formation with complete penetrance, whereas Wif1 and Brca2 can induce OS in just a small percentage of mice [16, 17, 58, 70]. Furthermore, Apc , Ptch1 , and Prkar1a can only induce benign or low-grade malignant bone tumors, but not advanced OS [67, 68, 72].…”
Section: Understanding the Role Of Driver Gene Mutations In The Dementioning
confidence: 99%